Reconsidering the Optionality of Raising in Japanese Exceptional‐Case‐Marking Constructions. (20th April 2021) - Takahashi, Masahiko
Abstract: This article examines two arguments for the optionality of raising in Japanese exceptional‐Case‐marking constructions and proposes that certain observations can be accounted for even if we assume that raising is obligatory. Specifically, I contend that the distributions of exceptionally Case‐marked wh negative‐polarity items and of embedded adjuncts, both of which have been cited as evidence for the optionality of raising, can be reconciled with the obligatory‐raising analysis. I propose (i) that the distribution of wh negative‐polarity items obeys a condition defined in terms of Transfer domains and (ii) that A‐movement allows adjuncts to take a "free ride." Some consequences for the licensing of wh negative‐polarity items and for free‐ride effects are also discussed.